Contextual learning using Balinese salak (Salacca zalacca) probiotic drink to enhance science literacy in microbiology - Nadya Treesna Wulansari; I Putu Gede Sutrisna; Ni Wayan Kesari Dharmapatni (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
The implementation of microbiology learning in higher education is still dominated by conventional, lecture-based methods that emphasize rote memorization rather than critical thinking and problem-solving. This limits students’ ability to develop scientific literacy, particularly in applying microbiological concepts to analyze real-world environmental and health-related issues. Studies that specifically explore the utilization of probiotic products made from local plants as learning media in an effort to improve science literacy, especially in the field of biology, are still relatively limited. This study aims to investigate the effect of implementing contextual based learning through the utilization of probiotic drinks made from Balinese salak fruit (Salacca zalacca) on improving students science literacy in microbiology topics. This research is a pre-experimental study with One Group Pretest-Posttest design with a total sample of 60 people. Data analysis in this study was Paired Sample T-Test. The results of the analysis showed a significant increase in the average value of the pretest (65.91) and posttest (80.75). Contextual approach through the integration of Balinese salak fruit probiotic drink in microbiology learning proved effective in improving students’ science literacy significantly (p < 0.001). This approach contributes significantly to the improvement of student’s literacy, connection with the local context, and the ability to apply scientific concepts in everyday life.Abstrak. Pembelajaran mikrobiologi di pendidikan tinggi masih didominasi oleh metode konvensional berbasis ceramah yang menekankan hafalan dibandingkan pemikiran kritis dan pemecahan masalah. Hal ini membatasi kemampuan mahasiswa dalam mengembangkan literasi sains, terutama dalam mengaplikasikan konsep mikrobiologi untuk menganalisis permasalahan nyata di bidang lingkungan dan kesehatan. Kajian yang secara spesifik mengeksplorasi pemanfaatan produk probiotik berbahan dasar tanaman lokal sebagai media pembelajaran dalam upaya meningkatkan literasi sains, khususnya dalam bidang biologi, masih relatif terbatas. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan pembelajaran berbasis pendekatan kontekstual dengan memanfaatkan minuman probiotik dari buah salak Bali (Salacca zalacca) terhadap peningkatan literasi sains mahasiswa pada topik mikrobiologi. Penelitian ini merupakan studi pre-eksperimen dengan desain One Group Pretest-Posttest dengan jumlah sampel sebanyak 60 orang. Analisa data dalam penelitian ini adalah Paired Sample T-Test. Hasil analisis menunjukkan adanya peningkatan signifikan pada nilai rata-rata pretest (65,91) dan posttest (80,75). Pendekatan kontekstual melalui integrasi minuman probiotik buah salak Bali dalam pembelajaran mikrobiologi terbukti efektif dalam meningkatkan literasi sains mahasiswa secara signifikan (p < 0,001). Pendekatan ini memberikan kontribusi nyata dalam peningkatan literasi mahasiswa, keterkaitan dengan konteks lokal, serta kemampuan mengaplikasikan konsep ilmiah dalam kehidupan sehari-hari.